Penerapan Prinsip Akuntabilitas Dan Transparansi Dalam Mengelola Keuangan Desa - Rimi Gusliana Mais; Lini Palindri (Jurnal Akuntansi dan Governance, 2020)
This study aims how to know implementation principles of accountability and transparency in managing village finance in Government of Suka Damai Village, Plakat Tinggi District, Musi Banyuasin Regency. The research method use qualitative research method with a phenomenology type. The result of this study are that the Government of Suka Damai Village has implementation principles of accountability and transparency by involving villagers in deliberations to plan and discuss issues regarding village finance, implementation of village development, making and publishing financial reports,and overseeing the process of village financial management.